(untitled) (Victoria Journal of Management, 2025)
A combination of family and household responsibilities, access to professional development, gender bias, perceived weakness, organizational culture and attitude, and mentorship, among many others, can influence the women accountants’ career advancement. This study aims to identify factors affecting women accountants’ career advancement in Kathmandu Valley. The study conducted a questionnaire survey with 288 women accountants working inside the Kathmandu Valley in various institutions, including public and private, and used a correlational research design. The study found that gender discrimination, perceived weaknesses, and organizational culture and attitude negatively correlate with the career advancement of women accountants. However, access to professional development has significant positive relations with women accountant’s career advancement, but household and family responsibility and mentorship do not significantly affect women’s career advancement. Hence, organizations must cultivate inclusive cultures, offer flexible work arrangements, create unbiased opportunities among employees, develop positive attitudes toward women, and provide robust mentorship and sponsorship programs to enhance women’s career prospects in accounting. Addressing these factors can mitigate the challenges faced by women and promote a more equitable and diverse accounting profession.